Efficacy of 10-day decitabine in acute myeloid leukemia. (April 2021) - Bouligny, Ian M.; Mehta, Vivek; Isom, Scott; Ellis, Leslie R.; Bhave, Rupali R.; Howard, Dianna S.; Lyerly, Susan; Manuel, Megan; Dralle, Sarah; Powell, Bayard L.; Pardee, Timothy S.
Highlights: Real world outcomes using the 10 day decitabine regimen in AML are lacking. 10-day decitabine had an ORR of 36.1% in AML in the upfront setting. 10-day decitabine had an ORR of 25% in AML in the relapsed setting. Median survival was 6.6 months in the upfront setting and 4.8 in relapsed disease. Real world response data was comparable to clinical trials but survival was lower. Abstract: The azanucleotide decitabine is used in the treatment of acute myeloid leukemia (AML). Studies have shown conflicting results with 10-day regimens used in previously untreated AML patients. Additionally, there is little data on 10-day decitabine regimens in the relapsed setting. This study investigated outcomes of 108 adult patients with AML in the upfront and relapsed setting treated with a 10-day decitabine regimen. In the upfront group, the overall response rate (ORR, CR + CRi) was 36.1% and the median overall survival (OS) was 6.6 months, while the relapsed/refractory group had an ORR of 25% with an OS of 4.8 months. When analyzed with respect to cytogenetics, the upfront group featured an ORR of 28.1% with an OS of 9.4 months in the intermediate cytogenetic cohort compared to a 40.5% ORR and an OS of 5.4 months in the unfavorable cytogenetic cohort. An analysis of the relapsed/refractory group demonstrated an ORR of 26.3% with an OS of 7.9 months for intermediate cytogenetics versus 25.0% with an OS of 1.8 months in the unfavorable cohort. While these response rates are similar to previously published data, the median OS appears shorter.